1991
DOI: 10.1007/bf00982121
|View full text |Cite
|
Sign up to set email alerts
|

Response of total tannins and phenolics in loblolly pine foliage exposed to ozone and acid rain

Abstract: Tannin and total phenolic levels in the foliage of loblolly pine (Pinus taeda L.) were examined in order to evaluate the effect of atmospheric pollution on secondary plant metabolism. The trees were exposed to four ozone concentrations and three levels of simulated acid rain. Tannin concentration (quantity per gram) and content (quantity per fascicle) were increased in foliage exposed to high concentrations of ozone in both ozone-sensitive and ozone-tolerant families. No effect of acid rain on tannins was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 21 publications
0
15
1
1
Order By: Relevance
“…According to the present study and most earlier studies, O 3 did not have signi®cant eects on needle total phenolic concentrations (Jordan et al 1991;Kainulainen et al 1994Kainulainen et al , 1995aBooker et al 1996). However, higher concentrations of total phenolics (Tingey et al 1976;Kainulainen et al 1994) and some individual phenolic compounds (Kicinski et al 1988;Rosemann et al 1991) were found in conifers exposed to higher O 3 concentrations than used in the present study.…”
Section: Discussioncontrasting
confidence: 69%
“…According to the present study and most earlier studies, O 3 did not have signi®cant eects on needle total phenolic concentrations (Jordan et al 1991;Kainulainen et al 1994Kainulainen et al , 1995aBooker et al 1996). However, higher concentrations of total phenolics (Tingey et al 1976;Kainulainen et al 1994) and some individual phenolic compounds (Kicinski et al 1988;Rosemann et al 1991) were found in conifers exposed to higher O 3 concentrations than used in the present study.…”
Section: Discussioncontrasting
confidence: 69%
“…In addition to macroinvertebrate activity, secondary metabolites other than lignin (e.g., other polyphenolic compounds such as tannins) may override the effects of lignin and N concentrations on decay rate (Horner et al 1988). In urban areas tissue damage from air pollution, such as ozone, can result in the polymerization of carbonbased and N-containing secondary metabolites in plant foliage (Jordan et al 1991;Findlay et al 1996). Since our study makes an intraspecific comparison of leaf decay, a secondary factor affecting litter quality may be the cause of differences in decay rate between urban and rural derived red oak litter.…”
Section: Mass Lossmentioning
confidence: 96%
“…Different techniques detect different compounds with varying precision (Waterman and Mole 1994), requiring multiple techniques. Polymerized phenolics (tannins, lignin and bound phenolics that often accompany injury; Hasemann and Wild 1990, Jordan et al 1991, Koziol 1991, Violini et al 1992, Bi and Felton 1995, Findlay et al 1996 are particularly problematical. Furthermore, phenolic composition changes with development and environment, and differs between species (Hartley and Jones 1997).…”
Section: Phenolic Allocation and Concentrationmentioning
confidence: 98%